Clinical significance of serum mir-21,ca153 and cea in breast cancer - Rostam, Ali (Journal of Management and Science, 2021)
The Objective: one of the essential regulators of carcinogenesis is MicroRNA-21 (miR-21). Yet little light has been shed on its effectiveness as a tumor marker compared to the conventional ones. Comparing the diagnostic value of established tumor markers in breast cancer (BC) such as carcinoembryonic antigen (CEA) and CA153 with circulating level of miR-21 is the aim of this study. Methods:The study included 89 BC patients. Amplification of the circulating levels of miR-21 and miR-16 done using real-time PCR qualitative detection, while electrochemiluminescence assays was used to detect circulating levels of CEA and CA153. The diagnostic sensitivity for BC was compared between the three. Results: The serum miR-21 levels were high significantly BC patients, as the latter had much higher levels (P<0.001). the CA153 and CEA sensitivities were 15.73% and 22.47% respectively, while miR-21 Sensitivity and specificity were 87.6% and 87.3%. Conclusion:in BC patients miR-21 exhibits far higher sensitivity for diagnoses than both CEA and CA153. Thus especially in the early stages of BC, miR-21 can become a potential indicator for diagnosis, albeit the clinical stage, PR and ER statuses were not correlated in this study.